State-of-the-Art Javascript Language for Internet of Things - Oliveira, Fernando L.; Mattos, Julio C. B. (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
Currently, two technologies stand out in the field of research, the Internet of Things (IoT) and Javascript (JS). On one hand, IoT enables everyday objects to connect to the network, analyze, capture, and interact with the environment. On the other hand, we have JS, a programming language that was initially inside browsers but now it is being used in several backgrounds. This paper correlates IoT and JS technologies, showing how Javascript can be applied in the context of the Internet of Things. The survey has considered the work of the last ten years and presents state of the art from Javascript applied to the IoT-side.